Among Prestigious Edifices – on Ceramic Decorations and Mosaics in Poland Post-WWII - Kostuch, Bożena (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2017)
Ceramic materials may have multifarious applications, the visual arts being one of them. Furthermore, they have been often used in architecture for decorative purposes. In Poland, the application of ceramics in architecture reached its peak of popularity in the post-WWII period. It was used in mosaics, reliefs, architectural and sculptural details, as well as combined with other materials, like glass or stone. Ceramics was applied for creating various small decorative forms but also large compositions that covered even several dozen or several hundred square metres, in buildings that served various functions, and were situated either indoors or on their external facades. Amongst these, there are buildings which were both important for local communities and became landmarks for particular sites, like modern hotels, railway stations, theatres, museums or academies. The paper is focused on compositions executed for such prestigious edifices.